2009
DOI: 10.1021/jp905258x
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Line Solid-State NMR Characterizations of Sodium Alanates

Abstract: Pure NaAlH4, TiCl3-doped NaAlH4, and pure Na3AlH6 were characterized using 1H, 23Na, and 27Al solid-state NMR. The signal intensities and linewidths of 1H NMR spectra using several spin echo sequences and backprediction of a single pulse experiment were compared to find the optimal experiment to measure wide-line NMR spectra of the alanates. Second moment calculations using the Van Vleck equations compared with fits of the dipolar coupling line broadening confirm that NaAlH4 has a rigid crystal lattice. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 35 publications
5
43
0
Order By: Relevance
“…As dehydrogenation is followed a single release peak was observed and at maximum dehydrogenation a peak from metallic sodium occurs. Rehydrogenation restored the solid state NMR spectra indicating that process is reversible for a NaAlH 4 /C composite [101]. [102].…”
Section: Energy Materials -Lithium Ion Batteries Fuel Cells and Hydrmentioning
confidence: 78%
“…As dehydrogenation is followed a single release peak was observed and at maximum dehydrogenation a peak from metallic sodium occurs. Rehydrogenation restored the solid state NMR spectra indicating that process is reversible for a NaAlH 4 /C composite [101]. [102].…”
Section: Energy Materials -Lithium Ion Batteries Fuel Cells and Hydrmentioning
confidence: 78%
“…Our previous study of Na 3 AlH 6 showed that this may be a useful method to study different types of motions in complex metal hydrides. 56 A bulk 11 B spectrum of LiBH 4 was measured, and the result is shown in Figure 8. This spectrum was fitted with a quadrupolar powder pattern, which was simulated using SIMPSON.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The efforts made to solve this question span over a wide range of experimental techniques, including X-ray diffraction (XRD) [3][4][5][6], neutron diffraction [7], infrared (IR) and Raman spectroscopy [8], anelastic spectroscopy [9], differential scanning calorimetry (DSC) [10,11], electron paramagnetic resonance (EPR) [12], X-ray absorption spectroscopy (XAS) [13][14][15], X-ray photoelectron spectroscopy (XPS) [16][17][18], inelastic and quasielastic neutron scattering [19,20], nuclear magnetic resonance (NMR) [21,22], muon spin rotation (SR) [23], scanning electron microscopy (SEM) [3,18,24], and transmission electron microscopy (TEM) [24][25][26][27][28][29]. In addition, numerous density functional theory (DFT) calculations have studied possible Ti substitution scenarios in the bulk and at the surface of NaAlH 4 [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%